Leveraging sport and entertainment facilities in small- to mid-sized cities. Issue 2 (3rd April 2018) - Mason, Daniel; Sant, Stacy-Lynn; Misener, Laura
Abstract : Purpose: The purpose of this paper is to understand how, once a city has made a decision to build a new arena, local stakeholders envision the venue as a leverageable asset to achieve broader development goals through event hosting. Design/methodology/approach: A total of 66 semi-structured interviews were undertaken in 12 cities across Canada. Participants included city employees (parks and recreation, tourism), elected officials (current and former mayors, councilors), arena management, management from the local team (serving as anchor tenant), members of chambers of commerce and local business associations, prominent members of the local business community, and other politicians and relevant stakeholders (members of parliament, bloggers, journalists, educators, and community activists). Interviews were transcribed and subject to coding to identify themes. Findings: Core themes were identified which captured how key stakeholders viewed the arena as an opportunity to leverage other events being targeted and held at the arena. This included: opportunities and benefits of hosting other events; the arena, competitiveness, and competition; partnerships and collaboration; capacity: knowledge and experience; and leveraging challenges. Originality/value: This study makes several important contributions to the literature. First, it examines sports facilities in smaller cities, a subject more widely studied in larger, "major league" cities. Second, it takes a different approach to understanding leveraging, examining facilities rather than the event that the city is hosting or the franchise that plays in the city. Third, it examines a context where the facility has been built for a sports team, and not for other sport and entertainment events that might be hosted there.